2012
DOI: 10.1021/ie301671z
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Differentiation and Crystal Growth Form of Friedel’s Salt Originated from Pozzolan and Portland Cement

Abstract: This paper has a scientific−technical character and deals with morphological comparison of Friedel's salt (Fs), which is a compound that is originated from two routes: C 3 A phase of Portland cement (PC) and Al 2 O 3 r− (reactive alumina) of pozzolans. The reaction courses are contrasted and the role of reactive components is discussed in detail. The results show a great difference in morphology of the Fs, relative to the function of its origin, which is directly related to its very different formation rate: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Furthermore, the UCS values of AS stabilized X2, which have the highest salinity and chloride content of the four samples, are about four times higher than those of the sample stabilized by PC P6. These results indicate that AS is more effective than PC P6 for stabilizing chloride saline soil (Talero and Trusilewicz, 2012). At the same time, the UCS values of the DS samples stabilized by AS are lower than those of the corresponding soil samples obtained from sites; however, the UCS values of the DS samples stabilized by PC P6 are higher than those of the corresponding soil samples.…”
Section: Ucs Of Stabilized Soilmentioning
confidence: 74%
“…Furthermore, the UCS values of AS stabilized X2, which have the highest salinity and chloride content of the four samples, are about four times higher than those of the sample stabilized by PC P6. These results indicate that AS is more effective than PC P6 for stabilizing chloride saline soil (Talero and Trusilewicz, 2012). At the same time, the UCS values of the DS samples stabilized by AS are lower than those of the corresponding soil samples obtained from sites; however, the UCS values of the DS samples stabilized by PC P6 are higher than those of the corresponding soil samples.…”
Section: Ucs Of Stabilized Soilmentioning
confidence: 74%
“…Some authors concluded that low salt concentrations accelerate the hydration process and high salt concentrations retard the process 1,3 . The Friedel's salt formation in cement pastes containing NaCl is also reported 1, 4,12,13 . The thermal analysis has been used as a tool to analyze the products hydrated formed in cement pastes containing salts 1, 3,10 .…”
Section: Introductionmentioning
confidence: 91%
“…Friedel's salt, as a chloride-containing AFm phase, can be formed by the chemical reaction between chloride and some AFm phases like monosulfoaluminate, monocarboaluminate and hemicarboaluminate (Sui et al, 2019). In addition, AFm phases also belong to the lamellar double hydroxide family exhibiting typical hexagonal platelets morphology, and previous works also confirmed that Friedel's salt crystallizes in a hexagonal manner with a particle size of several microns (Birnin-Yauri and Glasser, 1998;Li et al, 2017a;Talero and Trusilewicz, 2012). This largesize and hexagon-like Friedel's salt crystals might have a lower hardness, and grow with a higher porosity, as shown in Figure 10.…”
mentioning
confidence: 90%